Penyuluhan Tentang Pentingnya Kesehatan Reproduksi Pada Remaja Di Desa Sinyior Kecamatan Angkola Selatan - Dewi, Sri Sartika Sari; Melfi Suryaningsih; Rosmala Dewi; Anna Rizki Nasution; Lumongga Sari Harahap (Jurnal Pengabdian Masyarakat Aufa (JPMA), 2025)
Adolescence is a period that is considered vulnerable in life because it is a period of transition from child life to adult life which is full of turmoil. Becoming a teenager means going through a tough process that requires a lot of adjustments. The surge in body growth and maturation of reproductive organs is one of the big problems they face, including the reproductive organs which are vulnerable to reproductive tract infections, pregnancy, sexually transmitted diseases, and the use of illegal drugs. Strong sexual feelings cannot but be experienced by every teenager, even though the levels are different from one another. Likewise the ability to control it (Sarwono, 2010). The aim of this activity is to increase adolescent knowledge so that it can reduce the incidence of sexually transmitted infections and deviations in adolescents. This service activity was carried out at the Sinyior Village Office by providing counseling to young men and women. This community service activity was attended by 19 teenagers. The results obtained were 2 teenagers with good knowledge, 4 people with sufficient knowledge, and 13 people with poor knowledge. Through education regarding reproductive health, there has been an increase in adolescent knowledge regarding reproductive health in adolescents. Reproductive health education using the lecture method accompanied by posters and leaflets is a learning approach that provides a set of knowledge and skills needed to be able to make appropriate behavioral choices to avoid sexual deviations and reduce sexually transmitted infections.